دراسة تحليلية للعادات والثقافة الغذائية لمهندسي كلية الزراعة في جامعة تشرين - صقر إبراهيم; الأسد عمران; ضاهر سوسن (Latakia University Journal -Biological Sciences Series, 2019)
يمثل الغذاء هاجسا ً رئيسا ً لدى الكثير من حكومات العالم، وتسعى هذه الحكومات جاهدة إلى تأمين أمنها الغذائي، بشتى الطرق والوسائل . ونظرا ً لأهمية هذا الموضوع، فقد تم إجراء هذا البحث والذي يعد الأول من نوعه الذي يسلط الضوء على العادات الغذائية والثقافة الغذائية لدى المهندسين الزراعيين لما لهذا الموضوع من أهمية كبيرة بالنسبة للسكان بشكل عام. أجريت هذه الدراسة عام 2010 في كلية الزراعة من جامعة تشرين والتي يتواجد بها /146/ مهندسا ً. وأخذت عينة عشوائية بلغ قوامها /62/ مفردة يمثلون (42.5%) من المهندسين والمهندسات العاملين والعاملات في هذه الكلية, جمعت بيانات الدراسة باستخدام استمارة صممت لهذا الغرض باستخدام أسلوب المقابلة الشخصية, ولتحليل وعرض البيانات استخدم العرض الجدولي والنسب المئوية . بينت نتائج البحث أن (87.1%) من إجمالي العينة يفضلون طعام المنزل على الوجبات الجاهزة و(90.3%) من إجمالي العينة لا يتناولون المشروبات الغازية مع الطعام. وقد توصلت الدراسة إلى مجموعة من الاستنتاجات والتوصيات الهامة وبخاصةً فيما يتعلق بإقامة ندوات غذائية دورية تتضمن توعية الناس إلى الأغذية المضرّة بالصحة ، إضافة ً إلى التأكيد على دور وسائل الإعلام في نشر الوعي الصحي. Food is a prime concern of many governments around the world, and these governments strive to ensure its food security in various ways and means. Given the importance of this subject, it was decided to conduct this research, which is the first of its kind to highlight on the eating habits and nutritional knowledge of the Agriculture Engineers, and its great importance for the population in general. This study was done in 2010 in the Faculty of Agriculture at Tishreen University which has 146 engineers. A random sample of working engineers in the Faculty was taken, with total /62/ single which represents /42.5%/ of male and female workers in this Faculty. The data of this study was collected by using a form designed for this purpose using the method of personal interview, and to analyze and display data the tabular presentation of the percentages was used. The result of this research showed that /87.1%/ of the total sample preferred the home food instead of the prepared meals (fast food); and /90.3%/ of the total sample didn’t have soft drinks with their food. The study found a set of conclusions and recommendations, especially in making periodical food-awareness seminars, helping in educating people about unhealthy foods, in addition to stressing the importance of the role of media in spreading health awareness.